DUKUNGAN SOSIAL DAN STRATEGI MENGHADAPI MASALAH PADA PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Siti Rohmah Nurhayati; Siti Partini; Sigit Sanyata (LPPM UNY, 2010)
This research based on fact that there are heightened of domestic violence victims wowen and level of danger generated at themselves. Besides, this research leave from fact that there are less psychological research concerning domestic violence at women. This research is quantitative perspective with aim to know relation between social support with strategy face the problem at domestic violence victim women and elaborate source and also effective contribution of social support which accepted by domestic violence victim women. These research hypothesis are 1). there is relation between social support with strategy solve the problem at domestic violence victim women 2) there is positive relation between social support with strategy solve the problem which focusing on problem ( SMM-M) at domestic violence victim women, and 3) there is negative relation between social support with strategy solve the problem which focusing on emotion ( SMM-E) at domestic violence victim women. Research subjects were 34 domestic violence victim women which still stay in matrimony with his husband, have married minimize during 1 obtained year that collected through snowball technique. This Research location is in Special Region of Yogyakarta. Data collecting of this research use enquette method. Result of research shows that all of hypothesis are proven. These are: 1). There is relation between social support with strategy solve the problem at domestic violence victim women 2) there is positive relation between social support with strategy solve the problem which focusing on problem ( SMM-M). Besides, these research find that social support sources which most contribute on decision making strategy of domestic violence victim women are child and brother sources. As for contribution of SMM is 55,1 % and for SMM-E 58,5 %.